Infection-Induced Elevated Plasma Perampanel in a Patient with Hemimegalencephaly - Yuya Kinoshita; Hiroe Ueno; Hirofumi Kurata; Chizuru Ikeda; Erika Hori; Takumi Okada; Tomoyuki Shimazu; Isao Fujii; Makoto Matsukura; Hoseki Imamura (Case Reports in Pediatrics)
Perampanel is a noncompetitive, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor antagonist. Herein, we report a case of increased perampanel plasma concentration and impaired consciousness triggered by an infection. The patient had refractory epilepsy associated with hemimegalencephaly. During adolescence, perampanel (maximum dose, 10 mg, oral), valproic acid, clobazam, and lacosamide were administered for seizure control. He was admitted to our hospital with high fever, impaired consciousness, and elevated perampanel plasma level (from 1,300 to 1,790 ng/mL), but with no increase in the concentration of other antiseizure medications. Further examinations (blood, cerebrospinal fluid, brain magnetic resonance images, and electroencephalogram) revealed no physical cause for impaired consciousness. After discontinuation of perampanel, his level of consciousness gradually improved. The pharmacokinetics of perampanel may be modified by both hemimegalencephaly and infection, resulting in an elevated plasma concentration of perampanel. This case underlines the importance of monitoring perampanel plasma concentration in patients with underlying brain disease who develop an infection.